2015
DOI: 10.1186/s12913-015-0977-y
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study of collaboration between perinatal and infant mental health clinicians and other service providers: Do they sit in silos?

Abstract: BackgroundWomen at risk of poor perinatal mental health benefit from coordinated approaches to care. Perinatal and infant mental health (PIMH) services have been established to support women with social and emotional needs. This paper examines the nature and extent of collaboration within two PIMH services in Australia.MethodsA convergent, embedded, mixed methods design was used. Two hundred and forty four medical records were reviewed, 13 professionals (six PIMH clinicians, two PIMH service managers, and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The review process identified 30 papers that met inclusion criteria (see Table ). Included studies regard the knowledge, skills and attitudes of midwives (Hauck et al., ; Higgins et al., ; Jones, Creedy, & Gamble, , ,; Lau, McCauley, Barnfield, Moss, & Cross, ; Legere et al., ; Mathibe‐Neke, Rothberg, & Langley, ; McCauley et al., ; Noonan, Doody, Jomeen, & Galvin, ; Noonan et al., ; Ross‐Davie, Elliott, Sarkar, & Green, ; Rothera & Oates, ), and student midwives (Higgins, Carroll, & Sharek, ; Jarrett, , ; Phillips, ); the effectiveness of educational interventions in improving knowledge and skills (Davies et al., ; Fenwick, Toohill, Slavin, Creedy, & Gamble, ; McLachlan, Forster, Collins, Gunn, & Hegarty, ; Reed, Fenwick, Hauck, Gamble, & Creedy, ); the delivery of counselling or psychosocial interventions by midwives (Clarke, King, & Prost, ; Fenwick et al., , ; Larsson, Karlström, Rubertsson, & Hildingsson, ; Toohill et al., ); and barriers and enablers to embedding midwife‐led mental healthcare in practice (Bayrampour et al., ; Fenwick et al., ; Gamble, Toohill, Slavin, Creedy, & Fenwick, ; Higgins et al., ; Myors, Schmied, Johnson, & Cleary, ; Myors et al., ).…”
Section: Findings/narrative Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…The review process identified 30 papers that met inclusion criteria (see Table ). Included studies regard the knowledge, skills and attitudes of midwives (Hauck et al., ; Higgins et al., ; Jones, Creedy, & Gamble, , ,; Lau, McCauley, Barnfield, Moss, & Cross, ; Legere et al., ; Mathibe‐Neke, Rothberg, & Langley, ; McCauley et al., ; Noonan, Doody, Jomeen, & Galvin, ; Noonan et al., ; Ross‐Davie, Elliott, Sarkar, & Green, ; Rothera & Oates, ), and student midwives (Higgins, Carroll, & Sharek, ; Jarrett, , ; Phillips, ); the effectiveness of educational interventions in improving knowledge and skills (Davies et al., ; Fenwick, Toohill, Slavin, Creedy, & Gamble, ; McLachlan, Forster, Collins, Gunn, & Hegarty, ; Reed, Fenwick, Hauck, Gamble, & Creedy, ); the delivery of counselling or psychosocial interventions by midwives (Clarke, King, & Prost, ; Fenwick et al., , ; Larsson, Karlström, Rubertsson, & Hildingsson, ; Toohill et al., ); and barriers and enablers to embedding midwife‐led mental healthcare in practice (Bayrampour et al., ; Fenwick et al., ; Gamble, Toohill, Slavin, Creedy, & Fenwick, ; Higgins et al., ; Myors, Schmied, Johnson, & Cleary, ; Myors et al., ).…”
Section: Findings/narrative Synthesismentioning
confidence: 99%
“…Studies in relation to the delivery of counselling or psychosocial interventions by midwives include a systematic review and meta‐analysis of 10 randomised controlled trials (RCTs) (Clarke et al., ), a single RCT (published in two papers) (Fenwick et al., ; Toohill et al., ), a qualitative interview study (Fenwick et al., ) and a national survey study (Larsson et al., ). Studies that outline barriers and enablers to embedding midwife‐led mental healthcare (other than knowledge and skills deficits), include two integrative reviews (Bayrampour et al., ; Myors et al., ) and three mixed method studies (Fenwick et al., ; Gamble et al., ; Myors et al., ).…”
Section: Findings/narrative Synthesismentioning
confidence: 99%
See 3 more Smart Citations